The Wisdom Encomium and Its Persuasive Function in the Book of Wisdom - Muszytowska, Dorota (Collectanea Theologica, 2021)
The Book of Wisdom is considered a coherent text characterised by genre syncretism. This article aims to examine the praise of wisdom in the Book of Wisdom for its persuasive functions. The encomium was used in the analysis as a typical genre of epideictic rhetoric. The text of the praise was analysed from the perspective of the features distinguishing this genre and determining its underlying structure. The analysis led to the conclusion that the author used the possibilities of the genre to teach the recipients what wisdom they should seek and to encourage them to take actions to achieve it. The encomium in the Book of Wisdom was subordinated to advisory rhetoric and is an essential element in the work’s structure.